O ensino das leis de Newton por meio de resolução de problema envolvendo atividades experimentais em um ambiente com diferentes interações sociais - Scomparin, Paulo Roberto (2019)
The purpose of this research is to stimulate the involvement, engagement and autonomy of students through interactions and exchange of experiences at various levels of socialization: groups, between groups, teacher groups and class groups, with the intention of bringing students in carrying out the proposed activities making physics teaching more attractive it's interesting. The survey was conducted with first year high school students, in a public school in the state of São Paulo. Of a qualitative nature, it involved research in which we report the results of the development of experimental activities involving Newton's three laws: Inertia, Fundamental Principle of Dynamics and Action and Reaction, considered essential and basic concepts for the introduction to the learning of Physical. We proposed a problematic text of dummy origin called "Accident in In this, the students investigate the death of the researcher, Dr. Caio Torres, while made the disposal of lunar rocks. The activity is divided into 3 main steps. After reading the introductory text, each group of students performs experiments that simulate aspects of the accident, organized by a roadmap. In the next step, called intergroups, there is the exchange of information between groups that performed different experiments. In the final stage, the groups return to their original formations and formulate their conclusions. presenting a solution to the proposed problem. Through reports written by the students and field notes, we observed as a result that most demonstrated interest in carrying out the activity, getting involved in the proposed dynamics and showing engagement in interactions. We also observed signs of appropriation of the concepts basic mechanics. We note that the most challenging aspects of the proposal, which partly influenced the achievement of better results, were the manifestations of disaffected among some pairs.